Characterization of Pathogenic Microflora Causing Suppurative Septic Postpartum Complications: a Retrospective Cohort Study - O. V. Lazareva; S. V. Barinov; E. M. Shifman; L. D. Popova; L. L. Shkabarnya; Yu. I. Tirskaya; T. V. Kadtsyna; Yu. I. Chulovsky (Кубанский научный медицинский вестник, 2023)
Background. Suppurative septic postpartum complications occupy a leading position in the structure of causes of maternal mortality. Information about the characteristics of pathogenic microflora in various forms of complications and analysis of its resistance to antibacterial drugs determine the choice of rational therapy for this pathology.Objectives — to characterize the isolated pathogenic microflora in obstetric patients with suppurative septic postpartum complications.Methods. A retrospective cohort study was conducted at the Department of Obstetrics and Gynecology No. 2 of the Omsk State Medical University and the Department of Gynecology of the Omsk Regional Clinical Hospital. The study included 123 cesarean section patients treated from January 2013 to December 2022 who were divided into three groups: Group A — uncomplicated course of postpartum endometritis, n = 55; Group B — complicated forms of postpartum endometritis, n = 48: B1 — local complications (suture failure following cesarean section; parametritis) n = 29; B2 — pelvic peritonitis, n = 19; Group C — septic complications following critical obstetric conditions, n = 20. The pathogenic microflora of uterine and abdominal cavities was examined; the extent of contamination with a pathogen and sensitivity to antibacterial drugs were determined. The isolated microorganisms were identified using a MicroTax bacteriological analyzer (Austria), Vitek2 Compact (France) and routine methods; a disk diffusion method was employed to determine the sensitivity of microorganisms to antibacterial drugs. Calculations were performed using licensed Microsoft Office Excel 2013 and Statistica 10 programs (StatSoft Inc., USA). Nonparametric nominal data were compared using Pearson’s chi-squared test with p-value determination.Results. The pathogenic microflora was dominated by S. epidermidis, E. faecalis, E. coli, and E. faecium. In 2018–2022, a statistically significant decrease was observed in the isolation rate of S. epidermidis (p = 0.016), E. faecalis (p < 0.001), and E. faecium (p = 0.05). The highest resistance was exhibited by bacteria to the following antibiotics: S. epidermidis — cephalosporins (30.16%); E. faecalis — fluoroquinolones (33.33%); E. coli — cephalosporins (65.91%) and β-lactamase-resistant penicillins (40.91%); E. faecium — aminopenicillins (64.10%) and fluoroquinolones (50.0%); А. baumannii — fluoroquinolones, cephalosporins, carbapenems (100%), and aminoglycosides (84.2%). A contamination assessment revealed a high titer of isolated microorganisms in 60.53% of cases. We found a statistically significantly higher isolation rate of S. еpidermidis (p < 0.001), E. faecium (p = 0.01), and A. baumannii (p = 0.02) in the setting of pelvic peritonitis as compared to uncomplicated endometritis. In the case of suppurative septic complications due to critical obstetric conditions, the isolation rate was higher for S. еpidermidis (p <0.001), E. coli (p = 0.04), E. faecium (p = 0.005), A. baumannii (р<0.001), and K. рneumoniae (p = 0.04).Conclusion. The antibiotic resistance of pathogenic microorganisms calls for the development of new organ system support technologies and the use of methods capable of sorbing microorganisms and their toxins in the area of inflammation.